Modernizing Foreign Language Training for Future Teachers through the Use of Gamified Learning - Liudmyla Zakrenytska; Ruslana Melnyk; Tetiana Severina (Pedagogical Discourse, 2025)
This article investigates the effectiveness of gamification as an innovative approach within the educational process of higher pedagogical institutions, specifically focusing on its application in teaching foreign languages to future educators. The study provides a comprehensive review of both national and international scholarly works on gamification in higher education. In the study, we used a number of general scientific methods: analysis, synthesis, comparison, induction, deduction, generalisation, which contributed to a thorough study and analysis of the essence of gamification and the formulation of conclusions. Problem-solving methods made it possible to find out ways to implement game technologies in the process of teaching foreign languages in higher education.The authors analyze the concept of «gamification», defined as the use of game elements in non-game contexts, and substantiate the psychological and neurobiological mechanisms of its influence on students' cognitive interest, motivation, and brain functions. The role of gamification in activating the reward system and releasing dopamine, as well as its positive impact on cortisol levels, a stress hormone that improves attention and memory, is highlighted. The theoretical foundations of gamification are further explained by combining the ‘flow’ theory of Mihaly Csikszentmihalyi, behaviorist theories and self-determination theory. The key aspects of gamification, such as dynamics, mechanics, aesthetics and social interaction, were outlined in conjunction with its basic principles.Examples of available educational platforms, websites and applications, virtual/augmented reality technologies and artificial intelligence tools that facilitate gamified foreign language learning were analyze. It was emphasized that gamification modernizes the process of acquiring communicative competence in a foreign language, promotes intrinsic motivation, enhances engagement, improves learning outcomes and provides satisfaction from personal progress, thereby optimizing the interaction of all participants in the educational process. It was concluded that the introduction of gamification in foreign language teaching in pedagogical higher education institution is not just an innovation, but a strategic step towards the formation of a new generation of competent, motivated and adaptive educators capable of teaching languages effectively in the 21st century.